Wyrównywanie szans edukacyjnych w warunkach polskiej szkoły po 1989 roku. O potrzebie polityki wyrównywania szans edukacyjnych - Stępień, Natalia (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: The equalization of educational chances in Polish school after 1989. About the necessity of the policy of equal educational chances The article characterizes the actions, the aim of which is the equalization of educational chances which have been taken up by the educational authorities after 1989. The author focuses mainly on the educational reform which took place in 1999. One of the crucial aims of this reform was the equalization of educational chances. The author claims that due to the lack of efficiency of the equalization mechanisms, one should consider the implementation of a comprehensive program of policy of equal educational chances. The policy is a part of social policy and it does not affect only children who are in the school system. Key words: the equalization of educational chances, the policy of equal educational chances